Tingkat Stres Mahasiswa Program Studi Kedokteran Universitas Tanjungpura selama Pembelajaran Daring Masa COVID-19 dan Hubungannya dengan Keparahan Jerawat - Pratama, Elvin Felix; Rialita, Ambar; Mahyarudin, Mahyarudin (Cermin Dunia Kedokteran, 2024)
Background: During the COVID-19 pandemic, teaching and learning activities have to be conducted online. Many students have difficulty in dealing with online learning, and it may become a stress factor. Stress may cause several dermatological disorders such as acne. Objective: To determine the relationship between stress caused by online learning and acne severity during the COVID-19 period. Methods: A cross-sectional study with observational analytic research design. The population is Medical Study program students, Faculty of Medicine, Tanjungpura University. The sampling method uses the Proportionate Stratified Random Sampling technique with a minimum of 169 samples; 57 third-year students, 55 second-year students, and 57 first-year students. Stress level was measured with the MSSQ questionnaire, acne severity was measured with GAGS. Bivariate analysis used the Spearman correlation test. Results: A total of 62.7% of males and 46.8% of females experienced a moderate level of stress on online learning. A total of 66.7% of males and 56.4% of females had moderate acne. Spearman’s test for the relationship between online learning stress levels and acne severity obtained a value of 0.048 (p <0.05) and r = 0.152. Conclusion: The relationship between the stress level of online learning and the severity of acne among Medical Study program students at, the Faculty of Medicine, Tanjungpura University was very weak. Elvin Felix Pratama, Ambar Rialita, Mahyarudin. Stress Among Medical Study Program Students, Faculty of Medicine, Tanjungpura University during Online Learning in COVID-19 Period and Its Correlation with Acne Severity.